A case of dentigerous cysts occurring in bilateral mandibular second premolars - KURITA, Kenichi; ICHIHARA, Sachiko; NAKATSUKA, Kensuke; IMAI, Takao; TORII, Yuki; SEKI, Yasushi; WAKITA, Takeshi (Pediatric Oral and Maxillofacial Surgery, 2006)
Dentigerous cysts are developmental cysts. The pathogenesis of dentigerous cysts remains unknown; however some literature attribute the origin to degenerative changes in the reduced enamel epithelium following completion of the crown. Dentigerous cysts commonly occur unilaterally associated with the crown of permanent teeth. We report a case of dentigerous cysts occurring in mandible bilaterally in a 10-year-old-girl. A panoramic radiograph showed a well-defined radiolucent lesion that includes the crowns of unerupted bilateral mandibular second premolars under deciduos second molars. Computed tomography (CT) showed buccal cortical thinning and displacement of intra alveolar canal. Under general anesthesia, the cysts enucleated considering the preservation of involved permanent teeth. One year follow-up visit showed correct eruption of the teeth and stable occlusion.